Impact of Structured Lifestyle Intervention Program with Antigravity Exercise on Glycemic Control in People with T2DM - Dr. T MuthuVel; Dr. S. Karthikeyan (International Journal of Medical Research and Review, 2021)
Introduction: Diabetes mellitus (DM) is a common endocrinopathy and assumes significance for its ability to adversely affect the various internal organs. It can also derail the immune system of the affected. Abnormal insulin secretion and/or utilization, leads to hyperglycemia which has adverse effects on the heart, blood vessels, kidney, nervous system, eye and skin. To assess the effectiveness of structured vs unstructured lifestyle modification therapy in glycemic control (change in HbA1c value from baseline to the end of the intervention) in people with T2DM.Methods: This study is a randomized, controlled, parallel-group study with lifestyle modifications as intervention. Study was conducted for between Feb 2019 to Dec 2019 in the Department of General Medicine, Government Headquarters hospital, Tirupur.Results: A total of 70 participants, 30 to 60-year-old, diagnosed with T2DM for more than a year with HbA1c levels > 6.5 %, on a background of oral antidiabetic agents were enrolled after obtaining the informed consent. Mean age of Group A and Group B found 49.17±7.42 and 51.92±9.1. Male were predominant in the study. Mean weight, Mean FBS, Mean PPBS and Mean HbA1c are statistically significant between groups (p<0.05) at baseline. Group B with unstructured physical activity with walking, was beneficial (HbA1c reduction 0.30 %; p = 0.024), but no significant decline in HbA1c, whereas, in Group A with structured antigravity exercise, is associated with a significant HbA1c decline of 1.2 %. (p = 0.07865).Conclusion: Structured antigravity exercise training was more efficacious than unstructured physical activity in achieving controlled HbA1c levels. Although both structured and unstructured training provide benefits, only the former was associated with significant reductions in HbA1c levels. Hence, T2DM patients should be advised to follow structured antigravity exercise training & focused dietary intervention program.